Coke resistant and sulfur tolerant Ni-based cermet anodes for solid oxide fuel cells - Li, M.; Hua, B.; Jiang, San Ping; Li, J. (2017)
© The Electrochemical Society. Solid oxide fuel cell (SOFC), which can efficiently convert chemical energy in fuels into electricity, plays a critical role in solutions to the relentless increase in global energy demand. Its fuel flexibility is limited by the low tolerance of conventional Ni-based cermet anodes to carbon deposition and sulfur poisoning. This paper presents a brief review of our previous work on improving carbon and sulfur tolerance of conventional Ni-based anodes for direct utilization of hydrocarbon fuels. Two feasible methods of incorporating a spinel-based on-cell reforming layer and impregnating barium cerate-based perovskite nanoparticles are adopted to modify Ni-based anodes. The electrochemical performance and carbon/sulfur tolerance are both remarkably improved. This review is expected to provide insights based on our recent results for promoting the development of carbon/sulfur tolerant anodes with high electrochemical activity for direct hydrocarbon SOFC.